Right To The City: Lagos, An Emerging Revanchist City In Nigeria? - Nwanna, Chinwe R. (Advances in Social Sciences Research Journal, 2018)
Right to the city is a concept that is part of discourse about contemporary urban development with its resultant social inequalities while revanchist city refers to a city that has zero tolerance policies against the poor, marginalized and downtrodden people who are seen as threats to urban order and culprits of urban decay. Gathering data from secondary sources, this chapter x-rayed programmes and policies executed by Lagos State between 2007 and 2015. The results showed that various processes of neoliberal restructuring of Lagos city had threatened democracy. Lagos State government, in a bid to revitalize the city, demolished some slum areas and evicted the residents because it would no longer tolerate the existence of slums in the centre of the state with a megacity plan for a ‘world class’ Lagos. Beggars and the destitute were forcibly removed from the streets and taken to the rehabilitation centre in Ikorodu. Some were evacuated to their various states or countries. The result further revealed that a number of the beggars were sent to Kirikiri Prison while illegal aliens were expelled and repatriated to their homelands. It was also observed that riding commercial motor-cycles popularly known as ‘okada’ was banned in most parts of the city. Markets in Tejuoso and Oshodi were demolished and rebuilt beyond the reach of the former traders. Also banned was street trading. With all these inhumane strategies, this article concludes that Lagos is becoming a revanchist city and suggests that the state should jettison this neoliberal legislation and reconsider liberal policies characterised by redistributive policy, affirmative action and antipoverty legislation because constitutionally in Nigeria, every individual has the freedom to live in any region, state, or city of his/her choice.